Study of the influence of the addition of an exothermic mixture and the ratio of the components of the exothermic mixture on the melting indices at FCAW - Trembach, Bohdan; Grin, Aleksandr; Trembach, Illia (Lviv Politechnic Publishing House, 2020)
An important issue in the processes of strengthening and restoration of surfaces exposed to abrasive, abrasive-corrosive and hydroabrasive wear, using the process of self-protective flux-cored arc welding (FCAW), is to increase the productivity of hardfacing and the quality of the hardfacing metal. The literature review showed that one of the ways to increase the productivity of hardfacing and improve the quality of the hardfaced metal is to add an exothermic mixture to the core filler of flux-cored wire electrode. The effect of composition of filler core during FCAW on the fusion parameters, namely the addition of exothermic mixture (TM), the ratio of exothermic mixture components (CuO/Al), and the ratio of exothermic mixture oxidant to carbon content in the core composition (CuO/C) has been studied. It has been found that the optimum areas for the deposition rate (Gd), deposition factor (ad) and spattering factor (ψs) are observed for the following values of the core components: TM = 25…39, CuO/C = 5…6, CuO/Al = 3…4.
Keywords: hardfacing, FCAW-S, exothermic mixture, simplex-centroid design, deposition rate, deposition rate factor, spattering factor, composition